Preliminary Quantification of Spermatogenesis (Daily Sperm Production) and Epididymal Sperm Reserve in the Camel (Camel Us Dromedarius) in Nigeria (Journal of Science and Technology, 2016)
The scrotal contents of 109 camels (Camelus dromedaries) aged between 3-8 years were secured from abattoirs over a 12-month period and examined in Northern Nigeria. At slaughter, testes and epididymis were immediately collected examined for gross lesions and evaluated for paired testes weight (PTW), epididymal weight (EPW), daily sperm pro-duction (DSP) and epididymal sperm reserve (ESR). The mean weight of testes and epididymis were 87,32 ± 3.9g and 15.22 ± 3.12g respectively. The mean (±SD) DSP per gram of testicular parenchyma was 5.42 + 1.08 million cells and DSP per PTW aver-aged 4.80 + 1.74 billion sperm cells. The results of this study indicated that 1) prediction equations could be established for DSP and ESR, 2) the inter-correlations between PTW. DSP and ESR could be of special clinical significance in the pre-diction of reproductive potential of the one humped camel.